Introduction of psychological skills laboratory in medical education - Chen, Yoke Yong; Ting, Chuong Hock (Wolters Kluwer - Medknow, 2023)
Depression and anxiety are common psychological issues among university students, yet many of them hesitate to seek professional help due to stigma. Unfortunately, university curricula often lack self-help strategies to manage these challenges and provide timely support to those in need. To address this gap, we introduced the Psychological Skills Lab (PSL) component in the undergraduate medical curriculum, which emphasizes experiential learning to promote self-determination and autonomy in health promotion. The lab allows active interaction among students, lecturers, and peers through activities like presentations, peer reviews, in session practice, gratitude journals, group discussions, and role plays. PSL helps students develop skills, empathy, mindfulness, and self compassion through regular interactions. This innovative teaching approach raises mental health awareness and empowers students to assist others when required. Thus, by incorporating self-help measures into the curriculum, students are better equipped to manage their emotional well‑being while supporting those around them.